Implementation of Fuzzy Logic to Determine the Doneness of Beef Steak - Sista Naelly Adzimi; Robby Priaji Sakti; Aldiyansyah; Muhammad Ifan Al Aziz; Muhammad Fakhri Alauddin; Jimmy Mohamad Alpino Anak Gumay; Sesar Husen Santosa; Muhammad Danang Mukti Darmawan; Nanda Octavia (Batrisya Education, 2024)
This study aims to implement fuzzy logic in determining the doneness level of beef steak based on the inputs of roasting time and roasting temperature. The output of the developed system is in the form of maturity levels in the categories of